Didactic bases of professional development of the future teachers the musician in tool - performing classes - M.P. Nazarenko (Academy of Cognitive and Natural Sciences, 2006)
The article covers the didactic principles and methods of the instrumental and performing training of the future music teacher, the scientific and methodical and practical experience of the An Department student's training tn the instrumental classes is analyzed here.